The clinical and genetic aspects of six individuals with GH1 variants and isolated growth hormone deficiency type II - Huang, Xiaozhen; Chen, Hong; Shangguan, Huakun; Wu, Wenyong; Ai, Zhuanzhuan; Chen, Zhifeng; Chen, Ruimin (Frontiers in Endocrinology, 2024)
Background Isolated growth hormone deficiency type II (IGHD II) is an autosomal dominant disorder characterized by a GH1 gene variant resulting in a significant reduction in growth hormone (GH) secretion and a subsequent decrease of plasma insulin-like growth factor 1 (IGF-1) levels and eventual growth impairment. Objective This study aimed to identify causative variants in six Chinese families with IGHD II, exploring both clinical and genetic characteristics. Methods Detailed clinical data, including clinical presentations, physical charateristics, medical and family histories, as well as genetic test results, were systematically examined. Results Six children, comprising four males and two females, with a mean age of 4.64 ± 1.15 years, exhibited short stature with a mean height of -3.95 ± 1.41 SDS. Four of them had a family history of short stature, while one patient presented with pulmonary hypertension. All children demonstrated GH deficiency in growth hormone stimulation tests (mean peak GH value: 2.83 ± 2.46 ng/mL). Exome sequencing for the six patients and targeted gene sequencing for their family members revealed heterozygous variants in the GH1 gene, including Exon2-5del, c.334T>C, c.291 + 1G>A, c.291 + 2T>A, 1.5 kb deletion, and 1.7 kb deletion, with four variants being novel. Four patients underwent human recombinant growth hormone (rhGH) replacement therapy, initiating treatment at a mean age of 4.6 ± 0.7 years. The mean height increase in patients was 1.21 ± 0.3 SDS in the first six months of treatment and 1.79 ± 0.15 SDS in the first year. Conclusion Our findings contribute to expanding the genotypic and phenotypic spectra of individuals with IGHD II.